Highly efficient green light-emitting diodes from all-inorganic perovskite nanocrystals enabled by a new electron transport layer - Liu, Baiquan (2019)
Adopting proper electron transport layers (ETLs) is essential to high‐performance all‐inorganic perovskite light‐emitting diodes (PeLEDs). However, the effect of ETLs has not been comprehensively investigated in all‐inorganic nanocrystal PeLEDs, while 2,2′,2′′‐(1,3,5‐benzenetriyl) tris‐[1‐phenyl‐1H‐benzimidazole] (TPBi) is the most common ETL. Herein, a novel strategy is proposed to enhance the efficiency of nanocrystal PeLEDs. Tris(8‐hydroxyquinoline) aluminum (Alq3) is incorporated into TPBi to form a new ETL TPBi/Alq3/TPBi, simultaneously enabling charge balance and confinement. The green PeLED with new ETL exhibits a maximum external quantum efficiency (EQE) of 1.43%, current efficiency of 4.69 cd A−1, and power efficiency of 1.84 lm W−1, which are 191%, 192%, and 211% higher than those of PeLEDs with conventional ETL TPBi, respectively. Significantly, the EQE is 36‐fold higher than that of PeLED with high electron mobility ETL. Impressively, the full width at half‐maximum of electroluminescence emission is 16 nm, which is the narrowest among CsPbBr3 PeLEDs. The findings may present a rational strategy to enhance the device engineering of all‐inorganic PeLEDs.